2007
DOI: 10.1128/cmr.00027-07
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium malariae : Parasite and Disease

Abstract: SUMMARY A review of the life history of Plasmodium malariae, the quartan malaria parasite of humans, is presented. Much of the information is based on data obtained from induced infections in humans who were given malaria therapy for the treatment of neurosyphilis between 1940 and 1963. Prepatent periods (i.e., the time until the first day of parasite detection) fever episodes, and maximum parasitemias as a result of infection with P. malariae were obtained and are presented. Experimental and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
208
1
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(230 citation statements)
references
References 76 publications
4
208
1
8
Order By: Relevance
“…Once established, this syndrome does not respond to treatment and carries a high rate of mortality [16]. Moreover, Pf/Pm are known to co-infect together in endemic areas [17]. In this study, the most prevalent mixed infection was observed to be Previous studies have reported the sensitivity of PCR in very low parasitemia [11,18,19].…”
Section: Discussionmentioning
confidence: 55%
“…Once established, this syndrome does not respond to treatment and carries a high rate of mortality [16]. Moreover, Pf/Pm are known to co-infect together in endemic areas [17]. In this study, the most prevalent mixed infection was observed to be Previous studies have reported the sensitivity of PCR in very low parasitemia [11,18,19].…”
Section: Discussionmentioning
confidence: 55%
“…It was morphologically described as being similar to the human parasite P. malariae (33). Transmission studies with quartan parasites isolated from chimpanzees have shown that P. rodhaini is actually P. malariae (39).…”
Section: Discussionmentioning
confidence: 99%
“…Although P. malariae and P. ovale occur less frequently among human populations, they are widely distributed and their diagnosis has proven challenging due to their relatively low parasitemia and the morphology of blood stages, as well as the poor sensitivity of rapid diagnostic tests in non-falciparum species (1,2).…”
mentioning
confidence: 99%